Fruit Yield and Quality, and Irrigation Water Use Efficiency of Summer Squash Drip-Irrigated with Different Irrigation Quantities in a Semi-Arid Agricultural Area - Yasemin Kuslu; Ustun Sahin; Fatih M Kiziloglu; Selcuk Memis (Journal of Integrative Agriculture, 2014)
Fruit yield, yield components, fruit mineral content, total phenolic content, antioxidant activity and irrigation water use efficiency (IWUE) of summer squash responses to different irrigation quantities were evaluated with a field study. Irrigations were done when the total evaporated water from a Class A pan was about 30 mm. Different irrigation quantities were adjusted using three different plant-pan coefficients (Kcp, 100% (Kcp1), 85% (Kcp2) and 70% (Kcp3)). Results indicated that lower irrigation quantities provided statistically lower yield and yield components. The highest seasonal fruit yield (80.0 t ha−1) was determined in the Kcp1 treatment, which applied the highest volume of irrigation water (452.9 mm). The highest early fruit yield, average fruit weight and fruit diameter, length and number per plant were also determined in the Kcp1 treatment, with values of 7.25 t ha−1, 264.1 g, 5.49 cm, 19.95 cm and 10.92, respectively. Although the IWUE value was the highest in the Kcp1 treatment (176.6 kg ha−1 mm−1), it was statistically similar to the value for Kcp3 treatment (157.1 kg ha−1 mm−1). Total phenolic content and antioxidant activity of fruits was higher in the Kcp1 (44.27 μg gallic acid equivalents (GAE) mg−1 fresh sample) and in the Kcp2 (84.75%) treatments, respectively. Major (Na, N, P, K, Ca, Mg and S) and trace (Fe, Cu, Mn, Zn and B) mineral contents of squash fruits were the highest in the Kcp2 treatment, with the exception of P, Ca and Cu. Mineral contents and total phenolic content were significantly affected by irrigation quantities, but antioxidant activity was not affected. It can be concluded that the Kcp1 treatment was the most suitable for achieving higher yield and IWUE. However, the Kcp2 treatment will be the most suitable due to the high fruit quality and relatively high yield in water shortage conditions.